Knowledge and Attitude of Cervical Cancer Screening and Vaccination in Patients Attending Gynecology Outpatient Clinic at a Tertiary Care Hospital in Pakistan - Shamaun, Shamaila; Jaleel, Riffat; Gull, Yasmeen; Shahid, Afshan; Iqbal, Mehreen; Qazi, Tabinda Naseer (South Asian Journal of Cancer, 2022)
Background Cervical cancer is the third most prevalent female cancer in Pakistan; nearly 70% present at a very advanced stage of malignancy due to lack of awareness, proper screening, and vaccination. Therefore, we aimed to assess the knowledge and attitude toward screening, vaccination, and risk factors of cervical cancer in sexually active women of Pakistan.Methods This cross-sectional study was conducted at the gynecology outpatient clinic of a public sector hospital in Karachi, Pakistan, from December 2021 to March 2022. We included sexually active women with exception of diagnosed cases of cervical cancer, pregnancy, vaginal bleeding, and psychological disorder. Collected data were regarding demographic characteristics, awareness regarding cervical cancer, screening, human papillomavirus (HPV) vaccine, and risk factors, history of cervical screening, and wiliness to opt-in for cervical screening.Results We included 226 women with a mean age of 41.25 ± 10.54 years. The mean parity level was observed to be 3.8 ± 1.95. A majority of women were housewives by profession (88.9%) and uneducated (61.9%). Only 41.2% (93) of women were aware of cervical cancer, 33.6% (76) were aware of cervical screening, and only 15.9% (36) had a history of cervical screening. Only four women (1.8%) were aware of the HPV vaccine and 31% (70) showed intention to opt-in for cervical screening. A vast majority of women (96.9%) were not aware of the risk factors of cervical cancer.Conclusion(s) We have observed poor awareness regarding cervical cancer, HPV vaccination, and cervical screening among women in our population. Lack of awareness was not restricted to a certain segment but it prevails all across the demographic in our population.
Keywords: cervical cancer; cervical screening; HPV vaccination; awareness; knowledge; attitude; Pakistan